TANTANGAN ASPEK-ASPEK TERTENTU FILASAT BARAT MUTAHIR BAGI GENERASI PENERUS INDONESIA - Kertopati, Ton (Universitas Prof. Dr. Moestopo (Beragama), 2008)
What is involved when we say what people are doing and why they are doing it?. The background of the act, the situation which it occurred, a short statement about motives wiII offer same kind of answers to these. We want to inquire into the purely internal relationships, which the modem and new Western philosophies utilized by some Indonesian aspecially the young generations. Considering their possibilities of transformation for the ultimate ground or scheme of human actions.Â